A ludicidade e o ensino de ciências na educação em ciência, tecnologia e sociedade nos anos iniciais do ensino fundamental - Raiol, Kássia Cristina da Silva (Universidade Federal do Pará, 2024)
The intense transformations that have taken place in the contemporary world have produced new demands and challenges for science education, to form citizens who exercise active participation in a society increasingly influenced by science and technology. In this sense, this research aimed to understand and analyze how recreational activities allied to STS education, through themes, can favor scientific and technological literacy of children in the 1st Year of Elementary School. This is a qualitative study, of the participative research type, which presents pedagogical reflections and propositions about the teaching of science, through an educational product, structured in the format of a Pedagogical Notebook built in the format of an e-book, with based on assumptions of Playfulness and Education in STS, called "STS Education in the Initial Years of Elementary School: A playful proposal for the teaching of Personal Hygiene". The notebook is structured in two parts: the first with theoretical references discussed in the research and the second, where the proposed activities are organized, which problematize the theme: Can personal hygiene care save lives? Proceeding with the validation of this educational product by six teachers, postgraduates in the area of science, who work with science teaching in public schools in Belém-Pará, being the subjects of this research. For data collection, an instrument was developed using the Google Forms platform (sent by e-mail) that guided the analysis, reflections and contributions of the teachers, a questionnaire consisting of ten subjective (open) questions, which allowed the recording of of a broad evaluation of the educational product, consolidating the collection of research data. With the information collected, a Discursive Textual Analysis (DTA) was carried out to visualize the possible contributions of this research to those involved in science teaching. Thus, this research made possible understandings about the importance of giving the student the opportunity to build scientific and technological knowledge, to insert it in an ACT process, as well as to favor a citizen formation that develops abilities to interpret and apply such knowledge in real situations of the everyday life, contributing to their understanding of the world. In this sense, the association between playfulness and STS education proved to be a rich and promising path.